Eye lens monitoring programme for medical staff involved in fluoroscopy guided interventional procedures in Switzerland. (January 2019) - Nowak, Marie; Sans-Merce, Marta; Lemesre, Camille; Elmiger, Raphael; Damet, Jérôme
Highlights: An approach for eye lens dosimetry was verified using Dosiris and badges dosimeters. The relation between eye lens and whole body doses is discussed for medical staff. The eye lens dose is lower than the whole body dose in all services, but in urology. Hp(0.07) measured on the chest ensures compliance with the eye lens dose limit. This study confirms the validity of the Swiss approach for eye lens dosimetry. Abstract: Epidemiological studies indicate that radiation damages to the eye lens occurs at lower dose values than previously considered (Worgul et al., 2007; Chodick et al., 2008; Ciraj-Bjelac et al., 2010; Rehani et al., 2011; Vano et al., 2010)[1–5] . The International Commission on Radiological Protection lowered the equivalent dose limit value for the eye lens to 20 mSv/year (ICRP, n.d.)[6] . This new limit has been incorporated into the revised Swiss legislation[7] . Prior this change, it was agreed that if the effective dose limit was respected it would implicitly imply the respect of the limit to the eye lens, for penetrating radiation. The concept had to be reviewed in the light of necessary application of the new eye lens dose limit. The new Swiss legislation proposes to use the value of Hp (0.07) measured over the protective apron to estimate the eye lens dose. This study aims to investigate the validity of this approach for medical staff during fluoroscopy guided procedures. The results show that the ratio between thorax and eye lens doses varies greatly from one medical speciality to another, but also between surgeons within the same speciality. Moreover, for a given physician, the ratio varied over the periods of surveillance. Those variations confirmed the crucial influence of external parameters related to experience, practice and workload. The surveillance method is appropriate for most of the procedures performed in the department included in this study. Nevertheless, for the particular configuration in urology, the respect of the effective dose limit measured by the routine dosimetry does not allow direct compliance with the dose limit to the eye lens, unless appropriate protective eye wear gear are worn.